Undrained shear strength of soft clay reinforced with single non-encapsulated bottom ASH mixed with silica fume column (BASF) - Tan, Kah Yee (2019)
Soft clay is problematic soil that causes bearing capacity failure and excessive settlement, leading to severe buildings and foundation damage. Therefore, soil improvement is introduced to improve the engineering properties of the soft clay. In this study, bottom ash is used to replace the natural aggregate while silica fume is used as binder between bottom ash particles. This research is to investigate the role of single non-encapsulated bottom ash mixed with silica fume column (BASF) in improving the shear strength of kaolin by using laboratory scale model. Kaolin is being used as soil sample while BASF as the reinforced column. Laboratory tests are conducted to determine the physical properties of kaolin clay, bottom ash, and silica fume sample. Unconfined Compression Test (UCT) also used to test the shear strength of the reinforced kaolin samples. A total seven batches of kaolin sample had been tested and each batch consists of five specimens represent sample without BASF column, partially penetration and fully penetration for BASF columns with 50mm in diameter and 100mm in height. The diameter of reinforced column being used are 14mm and 20mm with heights of 60mm, 80mm and 100mm. The improvement of shear strength of BASF with area replacement ratio of 7.84% (14mm column diameter) and 16.00% (20mm column diameter) are 58.97%, 88.56%, 69.81%, and 19.19%, 38.73%, 32.81% at sample penetration ratio, Hc/Hs of 0.6, 0.8 and 1.0 respectively. It can be concluded that the shear strength of soft clay could be improved by the installation of the single non-encapsulated bottom ash mixed with silica fume column. However, the improvement of shear strength of 14mm diameter was increased more significant compared to 20mm diameter due to the small disturbance occurred since a small amount of kaolin was drilled and taken out from the samples and mobilization of the higher confining stresses in the column.